Frontier Overland Company : Dry Road to Nowhere - Book 2 - Johnstone, William W.; Johnstone, J. A. (Thorndike, Maine : Center Point Large Print, 2024)
"The Civil War is over. But Wyoming Territory is still a battleground for the native tribes who live there. Most folks avoid the area like the plague. But not former Texas Ranger Butch Keeling and his saloon fight buddy Tucker Cobb. They figured Wyoming would be the perfect place to launch the Frontier Overland Company -- a rough-and-ready stagecoach operation that dares to go where others fear to tread. Butch and Cobb arent afraid of much -- but their next stagecoach trip could change all that. And it just might be their last . . . The passengers are good people: Colonel McBride, whos delivering much-needed supplies to Fort Washington, and his lovely niece, who wants to visit her dying father. Even though the road to get there is overrun with armed Lakota, Cheyenne, and other deadly threats, Butch and Cobb are determined to help an old friend. Problem is, their worst enemy -- a power-hungry business rival and self-described King -- is out there. Waiting for them. Laying a trap to destroy their operation. And plotting to burn everything to the ground. Over Butch and Cobbs dead bodies . . ."--
Keywords: Stagecoach lines -- Wyoming; Fiction; Stagecoaches -- Fiction; Competition, Unfair -- West (U.S.); Fiction; Indians of North America -- West (U.S.); Fiction; Wyoming -- Fiction; Western fiction; Large print books